2022
DOI: 10.1590/2177-9465-ean-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade de jogo educativo para gestantes: conhecimento agregado e vivência das mulheres

Abstract: RESUMO Objetivos verificar a efetividade do jogo educativo para gestantes sobre seus direitos durante o trabalho de parto e parto; comparar o conhecimento das gestantes sobre seus direitos antes e após a aplicação do jogo e conhecer como foi para elas essa experiência. Método estudo quantitativo com análise qualitativa secundária. A coleta de dados ocorreu entre julho e setembro de 2019. Participaram 51 gestantes atendidas em duas Unidades Básicas de Saúde do município de Guarulhos. Utilizaram-se os testes K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Chinese research, focusing on young students with chronic diseases, attested to improvement of knowledge and care developed at home 5 . Other research, carried out in Brazil, also showed benefits in promoting cardiovascular health and knowledge of high-risk pregnant women, revealing developments also in adherence to treatment [2][3][4][5][6] . Furthermore, a game for nutritional support at home for children showed potential for providing health education with important gains in changing eating habits 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Chinese research, focusing on young students with chronic diseases, attested to improvement of knowledge and care developed at home 5 . Other research, carried out in Brazil, also showed benefits in promoting cardiovascular health and knowledge of high-risk pregnant women, revealing developments also in adherence to treatment [2][3][4][5][6] . Furthermore, a game for nutritional support at home for children showed potential for providing health education with important gains in changing eating habits 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Pesquisa chinesa, com enfoque em jovens estudantes com doença crônica, atestou a melhora do conhecimento e cuidados desenvolvidos em domicílio 5 . Outras pesquisas, desenvolvidas no Brasil, também mostraram benefícios para promover a saúde cardiovascular e o conhecimento de gestantes de alto risco, revelando evolução também na adesão ao tratamento [2][3][4][5][6] . Ainda, um jogo para apoio nutricional em domicílio a crianças apontou potencial para realizar educação em saúde com ganho importante na mudança de hábitos alimentares 7 .…”
Section: /16 Introduçãounclassified